75 The rising global burden of road injuries. (1st September 2016) - Boufous, Soufiane; Murray, Christopher JL; Vos, Theo; Lozano, Rafael; Naghavi, Mohsen; ,
Abstract : Background: The Global Burden of Diseases, Injuries, and Risk Factors Study, 2010 was established to provide reliable estimates on the leading causes of death and morbidity in populations worldwide and how these are changing over time. The aim of this paper is to present the findings of the study in relation to road injury in order to inform policy debates in the area of road safety. Methods: Information on death and morbidity was obtained from various sources (vital registration, verbal autopsy, surveillance, censuses, surveys, hospitals, police records, etc.) for 187 countries. DALYs were calculated as the sum of years of life lost (YLLs) and years lived with disability (YLDs). YLLs were calculated from age-sex-country-time-specific estimates of mortality and death by standardised lost life expectancy at each age. YLDs were calculated as prevalence of disabling sequelae, by age, sex, and cause; and weighted by new disability weights. Results: The number of deaths related to road injury increased by 43.6% from 908, 000 in 1990 to 1.329 million in 2010.This rise was mainly due to pedestrians deaths which increased by 62.3% from 284, 000 in 1990 to 461, 000 in 2010. Road injury was the leading cause of death among males aged 15–49 years in 2010. Road injury moved from being the 14th cause of YLL globally in 1990 to 8th in 2010. In term of DALYs, road injury also moved from 12th position in 1990 to 10th in 2010. Regional analysis shows road deaths in east Asia, south Asia, and eastern and western sub-Saharan Africa rapidly escalating over the past two decades, whereas in high-income areas with a history of road safety programmes such as western Europe, high-income North America, Australia and New Zealand road deaths have decreased. Conclusions: Despite various global road safety initiatives, the burden from road injury globally continues to rise, particulary amongst pedestrians. Continued efforts from all sectors are needed in order to address this growing challenge. *List of all collaborators (a few hundreds) and their affiliations will be provided as part of the presentation at the conference, if the abstract is accepted.